FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT UNTUK MENGGUNAKAN BANK SYARIAH DI WILAYAH JABODETABEK - Saffanah Aini Rahmani; Buchdadi, Agung Dharmawan; Yusuf, Muhammad (Journal Business Administration: Entrepreneurship and Creative Industry, 2023)
ABSTRACT: This study aims to measure the factors that influence the intention to use Islamic bank with the variables of religiosity, attitude, and intention to use. Data was collected using an online survey. This research was conducted in Greater Jakarta region involving 200 participants consisting of 28 men (14%) and 172 women (86%). Data analysis uses Structural Equation Modeling (SEM) to test the hypothesis. In total, there are two hypotheses. The findings from this research are religiosity has a positive and significant effect on attitude. In addition attitude has a positive and significant effect on intention to use.